DAMPAK TEMPAT PEMBUANGAN AKHIR SAMPAH TERHADAP GANGGUAN KESEHATAN DI MASYARAKAT KELURAHAN SUMOMPO KOTA MANADO TAHUN 2024 - Takahindangen, Gladys Evellin; Jilly Toar; Christian Bertom Pajung (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Final Waste Disposal Site is a place to process and return waste to environmental media in a safe manner for humans and the environment. The aim to be achieved in this research is to determine the impact of final waste disposal sites on health problems in the community of Sumompo Village, Manado City in 2024. This research was conducted using descriptive qualitative research methods. This type of research will produce discoveries that cannot be achieved using statistical processes. . The sample for this research consisted of 8 people using observation, interview and documentation data collection. The results of the research show that the impact of the existence of this landfill is very influential for people who live far and near, both ordinary people and people who work as waste workers/scavenger workers because it can affect health, causing the most common health impact found to be upper respiratory tract infections (ARI) and various diseases such as coughing, itching, shortness of breath and diarrhea. The conclusion is that there are people who feel disturbed when carrying out activities, there are people who accept and do not accept it, and there are changes in lifestyle and there are health problems experienced by people.